Reflections on the Way of Prayer - Bamberger, John Eudes (Cistercian studies quarterly, 2010)
The article discusses the early history of the Christian Church recapitulated in the life of Thomas Merton. It states that Merton discovered the incompatible ways in his chosen faith and decided to move to rural Kentucky to begin his Officium prayer in a different manner. It details the Christ-like belief and practice of Merton who was a strong follower of Christ and his paschal way of life.